Tourism and Hospitality Management Students’ Perceptions Towards Foreign Languages at State Universities in Zimbabwe: Case of Midlands State University - Chibaya, Tendai (Journal of Tourism Management Research, 2016)
This article, using the case of Midlands State University (MSU), Zimbabwe aims to unravel the perceptions of Tourism and hospitality management students towards foreign languages. The study of the students’ perceptions is an integral factor in the education of foreign languages as these students are the future workforce of the Zimbabwe’s tourism sector and beyond. It also aims at determining the benefits of studying foreign languages to both the students and the industry at large and the challenges students encounter when studying foreign languages. A survey was conducted on fourth year students who had already done Portuguese in their second year and currently doing French as foreign languages. A sample of sixty-nine students was targeted in May, 2015. The study revealed that most of the students had positive perceptions of studying French and Portuguese as part of their modules contributing to their academic achievement. The benefits of studying foreign languages were put forward as: employment benefits, memory improvement, improvement of communication skills, part of personal achievement, understanding of the new culture, networking and encourages mobility. However, fear, confusion, lack of confidence, limited financial resources as well as few hours allocated to French and Portuguese were highlighted as major challenges students confronted with in learning foreign languages.